THE EFFECT OF GREEN BANKING DISCLOSURE, ENVIRONMENTAL PERFORMANCE, AND COMPANY SIZE ON COMPANY VALUE: AN EMPIRICAL STUDY OF ISLAMIC COMMERCIAL BANKS IN INDONESIA (Proceeding of SINERGY, 2026)
This study was conducted to examine the relationship between disclosure of green banking practices, environmental performance, and company scale on company value in Islamic Commercial Banks in Indonesia. “Company value in this study is represented by the Price to Book Value (PBV) ratio. The approach used is quantitative with a causal associative research type. The study population includes all Islamic Commercial Banks listed on the Indonesia Stock Exchange. The sample was determined using a purposive sampling method on 11 banks during the observation period, resulting in 33 observational data sets. The data used are secondary data sourced from annual reports, sustainability reports, and official publications of the Financial Services Authority (OJK). Measurement of green banking disclosure and environmental performance is carried out using a disclosure index based on OJK provisions through a content analysis method, while company size is measured using the natural logarithm of total assets. Data processing and analysis in this study were carried out using multiple linear regression methods assisted by SPSS software. The results of the study indicate that green banking disclosure, environmental performance, and company size simultaneously influence company value. However, individual test results indicate that only environmental performance has a positive and significant effect on firm value, while green banking disclosure and firm size do not show a significant effect. This finding suggests that Islamic banking investors respond more to tangible environmental performance than simply green banking disclosure and firm asset size.